Bioprinting with bioactive alginate dialdehyde-gelatin (ADA-GEL) composite bioinks: Time-dependent in-situ crosslinking via addition of calcium-silicate particles tunes in vitro stability of 3D bioprinted constructs - Heid, Susanne; Becker, Kevin; Byun, Jiwon; Biermann, Isabell; Neščáková, Zuzana; Zhu, Hui; Groll, Jürgen; Boccaccini, Aldo R. (Bioprinting, 2022)
The development of hydrogels suitable for biofabrication is essential to enable advanced approaches for tissue engineering and regenerative medicine. Applications in both hard and soft tissues require tailor-made bioinks to guide cellular behavior in a 3D matrix. In this study we aimed to enhance the stability and adjust the degradation behavior of alginate dialdehyde-gelatine (ADA-GEL) hydrogels using an in-situ crosslinking mechanism additionally to external crosslinking. To test this approach, we added 0.1 and 0.5% (w/v) bioactive inorganic fillers (BIF) based on sub-micrometric calcium-silicate particles to ADA-GEL hydrogels. Such BIF release bivalent Ca2+ ions which can internally crosslink alginate chains and tune the degradation of the hydrogel over 28 days of incubation. It was found that pure ADA-GEL dissolved quickly after the first day while the composite hydrogels remained stable exhibiting reduced degradation (20–50% of the initial weight). 3D (bio)printing of composite bioinks revealed improved printing accuracy, 3D shape fidelity as well as cell spreading throughout the entire matrix during 14 days of evaluation. Chemically, BIF did not seem to have an influence on ADA-GEL Schiff's base bonds and also the mechanical properties of the composite hydrogels were comparable to those of pure ADA-GEL with Young's moduli of about 4 kPa. Comprehensive rheology measurements were carried out to determine printing parameters and the influence of BIF on the bioprinting process. We conclude that the novel hydrogel composition based on ADA-GEL system incorporating calcium-silicate BIF exhibits tunable behavior in vitro up to at least 28 days of incubation leading to improved stability and time-dependent cell behavior in 3D bioprinted constructs.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Alginate dialdehyde; Bioactive glass; Bioprinting; Composite bioink; Fibroblasts; Gelatin; Soft tissue engineering